Predicting modeling scenarios of climate change impact on the CO2 emissions from an Amazonian hydroelectric reservoir - Curtarelli, Marcelo; Stech, José; Lorenzzetti, João; Alcântara, Enner [UNESP]; Ogashawara, Igor (Springer Nature, 2020)
We simulated the carbon dioxide (CO2) emissions from a great Amazonian hydroelectric reservoir under future climate and land use land cover conditions using a three-dimensional ecological model. Future scenarios were developed taking into account the Representatives Concentrations Pathway (RCP) adopted by the Intergovernmental Panel for Climate Change (IPCC) in its fifth Assessment Report (AR5). To investigate the possible effects of future climate and land use changes on CO2 emissions, we compared our results with a previous study that simulated the carbon emissions under present climate conditions. The results showed that under moderate climatic changes scenario associated to the recuperation of natural land covers in the watershed (i.e., increase in forestry areas) the CO2 emissions are estimated to be more than 100% higher than the current emissions in a specific season. On the other hand, in a more extreme climatic changes scenario associated to the expansion of agriculture and pasture areas, the estimates of CO2 emissions along the year decrease of 5% compared to current emissions. Our findings indicate that the processes such as eutrophication, mixing and stratification of water column and the water retention time will be key elements controlling the CO2 emission from Amazonian reservoirs in the future. We highlight that the CO2 emissions from future planed Amazonian hydroelectric reservoirs are uncertain and will be highly dependent of regional climate and LULC changes. Decision makers must to consider these two important factors in the environmental impact studies and comparisons with CO2 emission from other energy sources.
Keywords: Amazon; Carbon dioxide; Climate changes; Hydroelectric reservoirs; Land use and cover changes